2010
DOI: 10.1128/iai.01316-09
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Invasion by Orientia tsutsugamushi Is Mediated by Integrin Signaling and Actin Cytoskeleton Rearrangements

Abstract: Orientia tsutsugamushi, the causative agent of scrub typhus, is an obligate intracellular pathogen. Previously, we reported that the 56-kDa type-specific antigen (TSA56), a major outer membrane protein of O. tsutsugamushi, binds to fibronectin and facilitates bacterial entry into the host cell, potentially via an interaction with integrins. Here, we demonstrated that O. tsutsugamushi colocalizes with integrin ␣5␤1 and activates integrin signaling effectors, including focal adhesion kinase, Src kinase, and RhoA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 32 publications
2
71
0
Order By: Relevance
“…6). Previous studies reported that O. tsutsugamushi could bind to host fibronectin and utilize it for internalization via interactions with its outer membrane protein TSA56 (27,28). Our data also confirmed the TSA56 adhesion ability to host cells.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…6). Previous studies reported that O. tsutsugamushi could bind to host fibronectin and utilize it for internalization via interactions with its outer membrane protein TSA56 (27,28). Our data also confirmed the TSA56 adhesion ability to host cells.…”
Section: Discussionsupporting
confidence: 79%
“…Recent studies have shown that the scrub typhus pathogen, O. tsutsugamushi, can bind to fibronectin (Fn) via a major antigenic membrane protein, TSA56 (27,28). The ADIII and adjacent C-terminal region of TSA56 was sufficient for Fn interaction and prohibiting Fn-enhanced invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that several intracellular pathogens utilize Src kinase for internalization and dissemination (16,32,51,61,78,90), we tested whether specific Src family kinase (SFK) inhibitors inhibited B. burgdorferi internalization in vitro. Specifically, Src kinase activity is required for the internalization of Neisseria spp.…”
Section: Discussionmentioning
confidence: 99%
“…These diverse pathological changes in multiple organs are mainly due to focal or disseminated multiorgan vasculitis or perivasculitis of small blood vessels. The bacterium infects several types of nonphagocytic cells, such as endothelial cells and fibroblasts, as well as phagocytic macrophages, polymorphonuclear leukocytes (PMNs), and dendritic cells in vitro and in vivo (17)(18)(19)(20)(21). Previously, it was reported that increased autophagosomes were observed in PMNs after infection with O. tsutsugamushi (22).…”
mentioning
confidence: 99%